Nano-ZnO functionalized biochar as a superhydrophobic biosorbent for selective recovery of low-concentration Re(VII) from strong acidic solutions. (October 2019) - Hu, Hui; Sun, Longli; Wang, Tian; Lv, Chenguang; Gao, Yanling; Zhang, Yue-Fei; Wu, Huixiong; Chen, Xiaohui
Graphical abstract: Highlights: A novel nano-ZnO functionalized biochar composite was synthesized by a solvothermal and pyrolysis process. The superhydrophobic composite exhibited excellent selectivity and high efficiency to hydrophobic Re(VII). Surface superhydrophobicity and metal affinity played critical role to enhance Re(VII) adsorption selectivity and efficiency. Abstract: A novel nano-ZnO functionalized biochar with superhydrophobic surface was successfully synthesized and tested for selective recovery of Re(VII) anions in strong acidic solutions. The as-synthesized biochar was characterized by XRD, XPS, FT-IR, EDX, TEM, STEM-HAADF, SAXS, N2 adsorption-desorption isotherm and water contact angle measurements. The characterization results revealed that the functionalized biochar was composed of highly dispersed ZnO nanoparticles bound to biochar matrix and displayed superhydrophobicity with water contact angle of about 151–156°. Because of the synergistic effect of surface superhydrophobicity and metal affinity, the new biochar exhibited excellent selectivity and high efficiency to Re(VII) in the presence of various competing ions. Adsorption mechanism exploration found that inner-sphere complexation on homogeneous surface would be the dominant interaction, while liquid film diffusion was considered as the rate-controlling step in the sorption process. Due to its excellent selectivity, high efficiency and easy synthesis process, the obtained superhydrophobic biosorbent is ideal candidate for Re(VII) recovery from copper smelting acidic wastewater.